2019
DOI: 10.1590/0001-3765201920180459
|View full text |Cite
|
Sign up to set email alerts
|

6-Bromoindirubin-3’-oxime promotes osteogenic differentiation of canine BMSCs through inhibition of GSK3β activity and activation of the Wnt/β-catenin signaling pathway

Abstract: Bromoindirubin-3'-oxime promotes osteogenic differentiation of canine BMSCs through inhibition of GSK3β activity and activation of the Wnt/β-catenin signaling pathway. An Acad Bras Cienc 91: e20180459.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
(23 reference statements)
1
17
0
Order By: Relevance
“…In contrast, LEF1 was shown to be overexpressed in the initial and later phases of bone repair [17]. The activated Wnt/β-catenin pathway can promote the osteogenic differentiation of BMSCs [18]. Although the activation of the Wnt/β-catenin pathway results in bone formation, increased bone mass results from excessive bone formation rather than bone resorption in both situations [19].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, LEF1 was shown to be overexpressed in the initial and later phases of bone repair [17]. The activated Wnt/β-catenin pathway can promote the osteogenic differentiation of BMSCs [18]. Although the activation of the Wnt/β-catenin pathway results in bone formation, increased bone mass results from excessive bone formation rather than bone resorption in both situations [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, as observed for osteogenesis, the simultaneous use of inhibitors and C 2 S NPs could improve the effect of the inhibitor on the expression level of β-catenin. This phenomenon might be related to our observation that C 2 S NPs could be taken into the nucleus by cells, followed by direct activation of the transcription factor β-catenin and mediation of BMSC osteogenic differentiation [ 39 ]. Simultaneously, we also found that the expression of ULK1 was upregulated in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have found that AMPK can directly or indirectly inhibit mTOR activation of the ULK1 pathway, while the Wnt/β-catenin pathway has been found to be related to osteogenic differentiation. We speculated that C 2 S NPs could activate autophagy through activation of the AMPK/ULK1 pathway and then activate the Wnt/β-catenin pathway to promote osteogenesis [ 39 ]. We verified the expression of related proteins in this pathway by Western blotting after coculture of C 2 S NPs and BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…We used a Wnt signaling activator (6-bromoindirubin-3ˊ -oxime (BIO) ( Zhao et al, 2019 ) and pcDNA3-cMyc ( Ricci et al, 2004 ) to enhance c-Myc expression in OACM5.1C cells which showed lowest c-Myc expression in our panel of EC cell lines tested. BIO is a novel small molecule inhibitor of glycogen synthase kinase 3 beta (GSK3β) and activator of the wnt/β-catenin pathway ( Zhao et al, 2019 ). Activation of the wnt/β-catenin pathway can upregulate c-Myc expression in various cells ( Li et al, 2012 ; Zhang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have demonstrated the efficacy C-Myc expression was manipulated pharmacologically and genetically. We used a Wnt signaling activator (6bromoindirubin-3ˊ-oxime (BIO) (Zhao et al, 2019) and pcDNA3-cMyc (Ricci et al, 2004) to enhance c-Myc expression in OACM5.1C cells which showed lowest c-Myc expression in our panel of EC cell lines tested. BIO is a novel small molecule inhibitor of glycogen synthase kinase 3 beta (GSK3β) and activator of the wnt/β-catenin pathway (Zhao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%